DETERMINANTS OF TIMELINESS OF FINANCIAL REPORTING: AN EMPIRICAL STUDY ON PROPERTY AND REAL ESTATE ISSUERS IN INDONESIA - Arry Eksandy; Riski Ulan Sari; Tri Yulaeli (RADJA PUBLIKA, 2025)
This study aims to analyze the influence of profitability, company age, and financial distress on the timeliness of the publication of audited financial statements in property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2022 period. The sample was determined by the purposive sampling method, so that 19 companies were obtained as research samples. The analysis method used was multiple linear regression with the help of EViews version 12 software. The results of the study show that partially, the variables of profitability and company age do not have a significant effect on the timeliness of financial report publication. On the other hand, financial distress has been proven to have a significant effect on the timeliness of the publication of audited financial statements. Simultaneously, the three independent variables have a significant effect on the dependent variables. A determination coefficient value (R²) of 0.81 indicates that 81% of the variation in the timeliness of financial statement publication can be explained by profitability, company age, and financial distress, while the remaining 19% is explained by other variables outside the model. These findings provide implications for company management and regulators in improving the transparency and accountability of financial reporting in the property and real estate sectors.